ANTIMICROBIAL ACTIVITY OF SCHIFF BASE OF OFLOXACIN - Verma, Stuti; Sirbaiya, Anup K.; Pandeya, Surendra N. (Asian Journal of Pharmaceutical Research and Development, 2013)
The Antimicrobial activity of Schiff base of ofloxacin, was investigated in vitro under aseptic conditions, using the disk diffusion method, against various gram positive and gram negative pathogenic microorganisms such as Pseudomonas aeruginosa (P.A.), Staphylococcus aureus (S.aureus), Helicobacter pylori (H. pylori), Escherichia coli (E. coli), Methicillinresistant Staphylococcus aureus (MRSA) and some fungal strains such as, Aspergillus fumigatus, Pneumocystis carinii and Aspergillus niger. A series of these compounds were prepared and have been shown to inhibit pathogenic growth, judging from the area of the zone of inhibition. The area of zone of inhibition of compounds found from 6 mm2 to 48 mm2 . Among the synthesized compounds; Compound SV-14 (6-[(4,7-Dimethyl-benzothiazole-2-carbothioyl)-hydrazono]-8-fluoro-3-methyl9-(4-methyl-piperazin-1-yl)-2,3-dihydro-6H-1-oxa-3a-aza-phenalene-5- carboxylic acid, showed good activity against P.A. (zone of inhibition 8 mm2 at 30 µg/ml), H. pylori (zone of inhibition 6 mm2 at 30 µg/ml) and E. coli (zone of inhibition 8 mm2 at 30 µg/ml); Compounds SV-8, SV-9, SV-10, SV-11, SV-12, SV-13 and SV-14 exhibited promising antibacterial activity. The target compounds showed in vitro antibacterial & antifungal activity less than reference antibiotic ofloxacin.